Synthesis, Characterisation and Biological Activities of Nitrogen-Sulphur Ligands and Their Transition Metal Complexes - Begum, Thahira (2008)
Synthetic compounds, especially those containing heterocyclic ring systems composed of nitrogen and sulphur have been of great interest due to their versatility as medicinal drugs. In view of this, three new isomeric dithiocarbazate ligands, S-2-methylbenzyldithiocarbazate, S-3-methylbenzyldithio- carbazate and S-4-methylbenzyldithiocarbazate, twenty-one Schiff bases derived from the isomeric dithiocarbazates with pyridine-2-aldehyde, 6-methylpyridine-2-aldehyde, 2-benzoylpyridine, di-2-pyridylketone, 2-acetylpyridine, 3-acetylpyridine and 4-acetylpyridine, and their Cu(II), Ni(II), Zn(II) and Cd(II) complexes have been successfully synthesized in a 1:1 mol ratio in an ethanol/acetonitrile mixture and characterized via various physico-chemical and spectroscopic techniques. The NMR and mass spectral analysis of the isomeric dithiocarbazates and their Schiff bases indicated the presence of a cyclised compound which was then identified as 2,5-bis(n-methylbenzylthio)-1,3,4-thiadiazole (n= 2,3 or 4). Elemental analyses, magnetic and spectral data indicate an octahedral geometry for all the metal complexes, except those derived from 3-acetylpyridine and 4-acetylpyridine which were expected to possess a distorted square-planar geometry. The structures of five Schiff bases, ten transition metal complexes and two thiadiazoles, namely 2,5-bis(2-methylbenzylthio)-1,3,4-thiadiazole and 2,5-bis(4-methylbenzylthio)-1,3,4-thiadiazole were successfully elucidated via X-ray crystallographic analysis. The transition metal complexes had distorted octahedral geometries, coordinating via the pyridyl nitrogen, azomethine nitrogen and thiolate sulphur atoms of the Schiff bases in a mer configuration. The complexes have been evaluated for their biological activities against seven pathogenic microbials and two breast cancer cell lines, MCF-7 (Human breast carcinoma cells with positive estrogen receptor) and MDA-MB-231 (Human breast carcinoma cells with negative estrogen receptor). The complexes were mostly antibacterial, but were inactive against the fungal strains tested. The Schiff bases in this study were also completely inactive against the microbial strains but complexation with the transition metal ions had significantly increased the activity. The complexes were generally more active against the MCF-7 cell line as compared to the MDA-MB-231 cell line. Several correlations based on the structure-bioactivity relationship of the complexes have been made.